Characterization of fronts in the Western Mediterranean with a special focus on the North Balearic Front. (September 2021) - Barral, Quentin-Boris; Zakardjian, Bruno; Dumas, Franck; Garreau, Pierre; Testor, Pierre; Beuvier, Jonathan
Highlights: Thermal and haline fronts differ in the central part of the Algero-Provençal basin. Thermal fronts form a seasonal frontal zone from the Pyrenees almost toward Corsica. Salinity fronts form a quasi-permanent frontal zone from Mallorca to South Sardinia. The main salinity frontal zone shows a marked inter-annual variability. Deep Water Formation and Algerian Eddies spreading shift the haline front. Abstract: We focus on the characterization of thermohaline fronts in the Western Mediterranean, with a particular focus on the North Balearic Front (NBF), separating the Atlantic Waters that spread into the Algerian Basin from the saltier and colder waters of the Liguro-Provençal area. We use a simple gradient-based method of front detection applied to a 20-year (from June 1993 to June 2013) reanalysis of the Mediterranean. Statistics of daily frontal indices are used to identify areas of recurrent fronts, i.e., frontal zones. Comparisons with data from glider transects and remotely sensed sea surface temperature and altimetry data have been used to validate our approach from daily to seasonal and interannual time scales. Our method yielded two co-existing frontal zones in the area of the NBF. One with an almost permanent haline surface frontal zone extending southeastward from the Balearic Islands to Sardinia, representing the northern limit of the fresher Atlantic Water that spreads via instabilities of the Algerian Current and associated Algerian Eddies. Between years, its position shifts by about 1° of latitude, possibly due to processes associated with both the deep water formation in the Provençal Basin and the spreading of southern Algerian Eddies. The second frontal zone is seasonal and thermally driven extending off the northeast of Menorca to the northwest of Corsica. The Pyrenees Front, a sharp thermal front off Cap de Creus which marks the boundary between the warm surface waters of the Balearic Sea and the cooler waters in the Gulf of Lion in late summer, appears to facilitate the formation of the aforementioned seasonal thermal front through the northeastward advection of its waters toward the West Corsican Current. The divergent eastward extensions of the two frontal zones, and their differences in nature, structure, and spatio-temporal variability, call for a revisit of the NBF appellation and a clarification of its dynamics.